Relationship between personal characteristics and readiness to change in psychoactive substance addicts - FILONOVA, Oksana; KRUPELNYTSKA, Liudmyla (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The global trend of psychoactive substance (PAS) use continues to grow, with the emergence of new types of drugs and an increasing number of individuals with PAS addiction, including adolescents. In Ukraine, war serves as a risk factor for PAS use among both military personnel and the civilian population. Statistics indicate that only one in eleven individuals seeks treatment. Thus, studying the motivational sphere of individuals addicted to PAS – specifically, their readiness to change – is essential, as it serves as a predictor of treatment outcomes in this population. Methods. The study employed both theoretical methods (analysis and synthesis of scientific sources) and empirical methods, including: the "Self-assessment of mental states" questionnaire (modified by M. Horska), N.Harrington’s "Frustration Discomfort Scale", the BFI-10 (adapted by O.O. Serdyuk and O.B. Bazyma), the GAD-7 and PHQ-9 questionnaires, and the SOCRATES (Stages of Change Readiness and Treatment Eagerness Scale) by W. Miller. Statistical analysis included descriptive statistics, one-way ANOVA, and correlation and regression analyses. The study was conducted at the "New Way" rehabilitation center in Kyiv and included 62 participants: 12 women and 50 men. Results. Positive correlations were identified between readiness to change and personality traits such as anxiety, depression, neuroticism, aggressiveness, entitlement, and emotional intolerance. Neuroticism, aggressiveness, and depression were found to influence readiness to change. The most significant predictor of taking steps to overcome PAS addiction was problem recognition. Among men, the relationships between readiness to change and personality traits were consistent with those observed in the overall sample. Among women, readiness to change was correlated with openness to experience and extraversion. Conclusions. Individuals prone to anxiety and/or aggressiveness are more likely to recognize their substance addiction. Depression increases uncertainty and reduces readiness to change. Individuals who acknowledge their PAS problem are more likely to initiate treatment and make behavioral changes. In men, neuroticism and aggressiveness significantly influence problem recognition. In women, higher levels of extraversion are associated with reduced uncertainty and increased readiness to change. In both groups, the strongest predictor of readiness to change is the recognition of PAS addiction.